OP81 Estimating the Potential of Population Level Changes in Cholesterol and Blood Pressure for Reducing UK Coronary Heart Disease Mortality Rates: A Novel Modelling Approach. (17th September 2012) - O'Flaherty, M; Couch, P; Sperrin, M; Green, N; Ainsworth, J; Huffmann, M; Lloyd-Jones, D; Buchan, I; Capewell, S
Abstract : Background: Coronary heart disease (CHD) mortality is declining. However, population ageing and increasing obesity and diabetes might reverse this trend. Strategies to reduce salt and saturated fat intake could substantially decrease population-wide cholesterol and blood pressure levels and consequently reduce CHD events. Our aim was to explore the potential reduction in CHD mortality burden that might be achieved by population shifts in these risk factors. Methods: The novel Stock of Health (SoH) modelling approach integrates demographic and risk factor data from the Office for National Statistics and the Health Survey for England, and risk factor effects from the US Cardiovascular Lifetime Risk Pooling Project. The SoH approach estimates the latent "stock" of CHD-related health for each individual within the entire population of England and Wales (51 million). It then computes failure times for CHD mortality, allowing for multiplicative risk factor effects and competing mortality risks. We first simulated CHD deaths for England and Wales over the period 2000-2010. We then extended the simulations to 2030, and compared "FEASIBLE" and "IDEAL" population intervention scenarios, targeted to systolic blood pressure (SBP) and cholesterol under two future trend assumptions: I) assuming mortality rates in 2010 remain stable through to 2030, or II) assuming CHD mortality continue falling. Results: The mean simulated failure times closely mirrored those actually observed(1993–2004: men=72 vs. 71 years; women=74 vs. 75 years). In 2030, about 81200 CHD deaths are expected to occur under trend assumption I (+14% compared to 2010, reflecting population ageing) and 47600 under trend assumption II (–18% compared to 2010). SBP: For trend I, a FEASIBLE SBP reduction of 1mmHg and IDEAL reduction of –5mmHg could result in approximately 77300 (+9%, baseline: 2010)and 64500 (–9%, baseline: 2010) deaths respectively in 2030. Assuming falling trends (II), about 45500 (–22%, baseline: 2010) and 38300 (–34%, baseline: 2010) deaths would result in 2030 under the feasible and ideal scenarios respectively. Total cholesterol (TC): Under trend I, a FEASIBLE TC reduction of 0.1 mmol/l and IDEAL reduction of 0.5 mmol/l could result in about 74800 and 57000 deaths (5% and –20%) by 2030. Assuming trend II, the resulting deaths would be approximately 43900 and 33400 (–25% and –43%, baseline: 2010) respectively. Conclusion: Under both trend assumptions, the adoption of evidence-based dietary policies to reduce salt and saturated fat intake, resulting in population-wide decreases in blood pressure and cholesterol could result in substantial declines in forecasted CHD mortality.